Subwavelength superfocusing with a dipole-wave-reciprocal binary zone plate - Wang, Jun (2013)
We propose an idea of using a convergent dipole wave at the aperture, radiated from a dipole at distance of z0, to produce a perfect focusing at z0. We verified this idea through simulation and experimental observation. It is demonstrated that the zone plate designed based on the idea can provide a subwavelength superfocusing by effectively bending the surface waves in a Fresnel region of 100 nm to a couple of wavelengths and is suitable for a situation where a superresolution at a micro working distance is essential.